2021
DOI: 10.1101/2021.05.17.444363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Schema representations in distinct brain networks support narrative memory during encoding and retrieval

Abstract: Schematic prior knowledge can scaffold the construction of event memories during perception and also provide structured cues to guide memory search during retrieval. We measured the activation of story-specific and schematic representations using fMRI while participants were presented with 16 stories and then recalled each of the narratives, and related these activations to memory for specific story details. We predicted that schema representations in mPFC would be correlated with successful recall of story de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 83 publications
3
10
0
Order By: Relevance
“…This result is not entirely unexpected given that previous studies have found low levels of ISC in this region (Baldassano et al, 2017), especially in developmental populations (Lerner et al, 2019;Moraczewski et al, 2018). Furthermore, as has been found previously, it may be that only a subregion of the medial prefrontal cortex represents events (Baldassano et al, 2017;Brod et al, 2017;Masís-Obando, Norman, & Baldassano, 2022;Van Kesteren et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…This result is not entirely unexpected given that previous studies have found low levels of ISC in this region (Baldassano et al, 2017), especially in developmental populations (Lerner et al, 2019;Moraczewski et al, 2018). Furthermore, as has been found previously, it may be that only a subregion of the medial prefrontal cortex represents events (Baldassano et al, 2017;Brod et al, 2017;Masís-Obando, Norman, & Baldassano, 2022;Van Kesteren et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…3B ), emphasizing the importance of stimulus content. However, within each movie, regions with neural-behavioral segmentation alignment showed anatomical consistency with previous reports of regions that are sensitive to event changes (Baldassano et al, 2017; DuBrow & Davachi, 2016; Masís-Obando et al, 2021; Speer et al, 2003, 2007; Zacks et al, 2001). These included higher-order attention or default mode regions, including the temporoparietal junction (TPJ), prefrontal cortex (PFC), insula, parietal cortex, and cingulate.…”
Section: Resultssupporting
confidence: 86%
“…Past work has theorized that current perceptual information interacts with long-term knowledge about event categories (schemas and scripts) when forming and updating event models (Radvansky & Zacks, 2014). These stereotyped changes likely form shared boundaries (Baldassano et al, 2018; Masís-Obando et al, 2022) and reflect central hubs in the narrative (Lee and Chen, 2022). We suggest that individual-specific boundaries—i.e., those not shared among the majority of subjects—may reflect moments with more idiosyncratic meanings (i.e., a moment activating one’s own autobiographical memory) that lead to variable interpretations of a stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The contexts we encounter help us to construct situation models (Manning et al, 2015;Radvansky and Copeland, 2006;Ranganath and Ritchey, 2012;Zwaan et al, 1995;Zwaan and Radvansky, 1998) or schemas (Baldassano et al, 2018;Masís-Obando et al, 2022;Tse et al, 2007) that describe how experiences are likely to unfold based on our prior experiences with similar contextual cues. For example, when we enter a sit-down restaurant, we might expect to be seated at a table, given a menu, and served food.…”
Section: Introductionmentioning
confidence: 99%